Efficacy and safety of low dose ticagrelor in patients with acute coronary syndrome: a systematic review and meta-analysis. Issue 1141 (19th June 2020) - Chen, Qing; Zhang, Yuanyuan; Wang, Zhen; Wang, Shuai; Zhang, Hao; Wang, Yiwen; Lu, Chi; Xuan, Haochen; Wang, Chaofan; Li, Dongye; Xu, Tongda
Abstract: Our aim was to examine clinical trials, provide guidance to practitioners and estimate the efficacy and safety of two agents by comparing low dose ticagrelor with standard dose clopidogrel in patients with acute coronary syndrome. We systematically looked through Pubmed, Embase, the Cochrane Library, Wanfang data and CNKI for trials comparing low dose ticagrelor with standard dose clopidogrel for the treatment of patients with ACS since the database was created. The primary endpoint for efficacy was the rate of major adverse cardiac events (MACEs). The primary endpoint for safety was the rate of major bleeding events. We also evaluated platelet function between low dose ticagrelor and standard dose clopidogrel in ACS patients. From 6744 articles, 16 studies including 1629 patients met the inclusion criteria. In contrast with standard dose clopidogrel, low dose ticagrelor significantly reduced MACEs (OR 0.39, 95% CI 0.26, 0.58) and the difference was statistically significant (p<0.01). No difference was noted for major bleeding events (OR 1.16, 95% CI 0.43, 3.08) between the two agents (p=0.77). In addition, low dose ticagrelor showed lower platelet aggregation rate than clopidogrel (standardised mean difference (SMD) −0.68, 95% CI −0.83 to 0.53) (p<0.01). Platelet reaction units for low dose ticagrelor were much lower than those for standard dose clopidogrel (SMD −2.46, 95% CI −2.85 to −2.07) (p<0.01). In comparison with standard dose clopidogrel, low dose ticagrelor significantly lowered the incidence of MACEs, improved left ventricular ejection fraction, decreased left ventricular end diastolic dimension and did not expand the risk of major bleeding events or minor or minimal bleeding events in ACS patients with a considerable safety and efficacy profile. In addition, low dose ticagrelor was associated with dramatically lower platelet aggregation compared with standard dose clopidogrel.